PEMBELAJARAN STATISTIKA DENGAN MEDIA LKS BERBASIS POLYA DI SMP - A.R, CHRISTI PARNAMITA; KURNIAWAN, ANDRI; FATIRUL, ACHMAD NOOR; KRISTIANI, KRISTIANI; RS, RIKI SULIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Learning statistics material is considered difficult by students. One technique to improve understanding and problem solving abilities in statistics material is the polya step. The aim of this research is to describe statistics learning with polya-based worksheets in junior high school students. This type of research is classroom action research. The research subjects were 32 students consisting of 15 male students and 17 female students. The instruments of this research are test sheets, teacher observation sheets and student observation sheets. The data analysis technique used is qualitative data analysis which consists of data reduction, data presentation and drawing conclusions. The criteria for the success of this research are classical completeness more than equal to 75 and observation results in the good category. Based on the research results, it was obtained that the results of observing teacher activities were in the very good category, the results of student observations in the good category and classical completeness were 93.75%. The conclusion in this research is learning using media polya based worksheet with steps to understand the problem, prepare a plan, carry out the plan and check again. ABSTRAKPembelajaran pada materi statistika dianggap sulit oleh siswa. Salah satu teknik meningkatkan pemahaman dan kemampuan pemecahan masalah dalam materi statistika adalah dengan langkah polya. Tujuan penelitian ini adalah mendeskripskan pembelajaran statistika dengan LKS berbasis polya di siswa SMP. Jenis penelitian ini adalah penelitian tindakan kelas. Subjek penelitian sejumlah 32 siswa yang terdiri 15 siswa laki-laki dan 17 siswa perempuan. Instrumen penelitian ini adalah lembar tes, lembar observasi guru dan lembar observasi siswa. Teknik analisis data yang digunakan adalah analisis data kualitatif yang terdiri dari reduksi data, penyajian data dan penarikan kesimpulan.Kriteria keberhasilan penelitian ini adalah ketuntasan klasikal lebih dari sama dengan 75 dan hasil observasi pada kategori baik. Berdasarkan hasil penelitian diperoleh hasil observasi kegiatan guru pada kategori sangat baik, hasil observasi siswa pada kategori baik dan ketuntasan secara klasikal sebesar 93,75%. Kesimpulan dalam penelitian ini adalah pembeljaran dengan media LKS berbasis polya dengan langkah-langkah memahami masalah, menyusun rencana,melaksankan rencana dan mengecek kembali.